The Drama of Two Hopes: The Secular Versus the Christian Project for Europe - Wieczorek, Krzysztof (Ecumeny and law, 2024)
Europe is a community of people and nations with a still-to-be-determined identity. The project of European unity is a work in progress, and under the influence of historical circumstances it undergoes successive changes and looks for new inspirations.One of the key moments in the European history in the third millennium was broadening the EU in 2004 to include ten more countries, among them the Republic of Poland. Each of the new countries entered the community with its own set of hopes and expectations. In Poland, shortly before accession, the basic question was posed: what kind of Poland in what kind of Europe? Answers to this question were shaped by two types of inspiration: the first was based on the vision of the new evangelization of the continent, in which Poland could participate creatively thanks to its faithfulness to Christianity preserved through the centuries (Polonia semper fidelis); the second referred to secular traditions and the idea of a rational, just, free and democratic Europe, maintaining axiological neutrality. The text shows the dramatic divergence between these two projects for the Europe of the future, seen from the Polish perspective.